2022
DOI: 10.3390/brainsci12121688
|View full text |Cite
|
Sign up to set email alerts
|

Facial Emotion Recognition Deficit in Children with Moderate/Severe Obstructive Sleep Apnea

Abstract: Although previous studies have reported a facial expression classification deficit among adults with SDB, we do not know whether these findings can be generalized to children. In our study, children with sleep-disordered breathing (SDB) were divided into three groups: primary snoring (n = 51), mild obstructive sleep apnea (OSA) (n = 39), and moderate/severe OSA (n = 26). All participants, including 20 healthy controls, underwent an overnight polysomnography recording and the Emotional Expression Recognition Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…This exploratory study revealed that children with RSD were mainly affected in selective attention, cognitive flexibility, and inhibitory control, in addition to daytime impairment, providing useful information for the clinicians. In the second study [7], children with different types (i.e., primary snoring, mild obstructive sleep apnea, and moderate/severe obstructive sleep apnea) of sleep-disordered breathing (SDB) were requested to perform an emotional expression recognition task. The authors found that children with moderate/severe obstructive sleep apnea tended to exhibit problems in facial expression categorization, with a possible impact in their social communication ability.…”
mentioning
confidence: 99%
“…This exploratory study revealed that children with RSD were mainly affected in selective attention, cognitive flexibility, and inhibitory control, in addition to daytime impairment, providing useful information for the clinicians. In the second study [7], children with different types (i.e., primary snoring, mild obstructive sleep apnea, and moderate/severe obstructive sleep apnea) of sleep-disordered breathing (SDB) were requested to perform an emotional expression recognition task. The authors found that children with moderate/severe obstructive sleep apnea tended to exhibit problems in facial expression categorization, with a possible impact in their social communication ability.…”
mentioning
confidence: 99%